Metabolismo, desenvolvimento e composição química de Varronia curassavica Jacq. em função da supressão da irrigação - Bolina, Cristiane de Oliveira [UNESP] (2015)
Erva baleeira (Varronia curassavica Jacq.) is a medicinal plant native to Brazil. The essential oil has been used by the pharmaceutical industry for its antiinflammatory activity associated with α-humulene. This study aimed to assess the physiological, chemical and biochemical responses of V. curassavica plants to irrigation suppression. It was used micropropagated seedlings. The treatments consisted of the control (daily irrigation) and three levels of water deficit, expressed by water potential in leaf xylem (Ψw): T1 - control (Ψw: ~ -0.3 MPa), T2 - Ψw~ -1.0 MPa; T3 - Ψw~ -1.7 MPa and T4 - Ψw~ -2.5 MPa. Plants were evaluated for gas exchange, relative chlorophyll content, relative water content, biometrics analysis, biochemical characteristics, isotopic stability and chemical composition of essential oils. The results were subjected to analysis of variance and regression. In regression analysis, the most significant equations were selected based on the significance of the regression coefficients and on the highest coefficient of determination. Multivariate analysis was applied to the results of chemical composition of essential oils. The analysis of biometric variables (plant height, leaf area, yield of fresh mass of leaf, stem and the whole plant) evidenced reduction according to irrigation suppression. Irrigation suppression showed no influence ongas exchange, only the control was statistically different from the other treatments. The relative water content decreased linearly depending on the different levels of water potential, a reduction of approximately 80%. V. curassavica hasC3 photosynthetic mechanism. The highest oil yield (0.18%) was found in plants subjected to the lowest water potential (-2.5 MPa). The limits of the activity of superoxide dismutase and the highest proline ...